Expert validation of developed questionnaire on nutritional knowledge and supplement habits among disabled athletes in Malaysia / Nurul Athirah Mohd Azhari, Norazmir Md Nor and Haidzir Manaf - Mohd Azhari, Nurul Athirah; Md Nor, Norazmir; Manaf, Haidzir (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
Disability sport is becoming more popular worldwide which depicted in the increase participation from athletes. The increase participation exerted pressure to the athletes to achieve better sports performance. One of the factors in enhancing sports performances is nutrition. Proper diet is needed for athletes, as it is an essential component in optimizing the athletes’ physical development and sports performance. Identifying the nutritional knowledge and supplement habits among disabled athletes help to maximize the benefits of nutrition. Despite the importance of nutrition, there is no validated questionnaire in identifying the nutritional knowledge and supplement habits for disabled athletes in Malaysia. Thus, this study aims to develop and validate a questionnaire on nutritional knowledge and supplement habits among Malaysian disabled athletes, and to examine the reliability of the questionnaire. This paper intends to discuss the validation of the developed questionnaire specifically on expert validation. The target population of this study is Malaysian disabled athletes. Firstly, the questionnaire is developed and adapted from previous literature on both nutritional knowledge and supplement habits for disabled athletes. Then, the developed questionnaire undergoes translation process before proceeding with validation and reliability process. Expert validation required a panel of experts in sports nutrition, nutrition and dietitian fields and will be analyzed using the critical value of content validity ratio. The expected results of this study as a validated questionnaire on nutritional knowledge and supplement habits among Malaysian disabled athletes by the expert panel. In future research, the reliability of the questionnaire will be tested on 23 Malaysian disabled athletes, and their nutritional status will be identified. Hence, this study helps to promote the growth of disability sports in Malaysia and enhance the sports performance of disabled athletes in Malaysia through nutrition.